The Influence of Marketing Communication Through Instagram of Al Amjad Islamic College Medan on the Perception and Educational Preferences of Students' Parents - Muhammad Hafiz Pulungan; Suwardi Lubis; Syukur Kholil (Yayasan Adra Karima Hubbi, 2024)
Background. Educational institutions need marketing communication and have started to explore the world of social media for advertising by creating visual images or videos. Purpose. The purpose of this study was to analyze the influence of marketing communication of Al Amjad Islamic College through Instagram on parents' educational perceptions; analyze the influence of marketing communication of Al Amjad Islamic College through Instagram on parents' educational preferences; and analyze the influence of marketing communication of Al Amjad Islamic College through Instagram on parents' educational perceptions and preferences. Method. This study uses a quantitative approach with the correlation method. The research data collection technique used a questionnaire and the sampling technique used stratified random sampling with a sample size of 325 people from a population of 1748 students of Al Amjad Islamic College Medan. Results. The results showed that the advertising dimension marketing communication variable obtained a value of 88%. The facility dimension perception variable obtained a value of 87.1%. The peer dimension preference variable obtained a value of 87.7%. The results showed that the hypothesis H0 was rejected and Ha was accepted, namely that there was an influence of marketing communication through Instagram on perceptions at Al Amjad Islamic College with a large influence of 35.7%. This means that the two variables have a significant relationship with a moderate category. Conclusion. The results of the study indicate that the hypothesis H0 is rejected and Ha is accepted, namely that there is an influence of marketing communication through Instagram on preferences at Al Amjad Islamic College with a large influence of 37%. This means that the two variables have a significant relationship with a strong category. The results of simultaneous calculations show that the hypothesis H0 is rejected and Ha is accepted so that marketing communication simultaneously has a significant effect on educational perceptions and preferences.